ANALISIS HUKUM PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2012 TENTANG PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KITAB UNDANG-UNDANG HUKUM PIDANA - Ahmad Hadi Ikhrom; Mukhlis R; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Normatively, minor theft under Article 364 Book of the Criminal Justice Act, has become a key element of assessment standards to be qualified to the crime, ie, if the price of the goods stolen is not more than two hundred and fifty dollars. However, sociologically, the application of the article applied to the perpetrators of the theft to the value of the stolen goods prices more than two hundred and fifty dollars to be based on Supreme Court Regulation No. 2 of 2012.The purpose of writing this thesis, namely: First, to know the concept of minor criminal offenses before and after the Supreme Court Regulation No. 2 of 2012. Secondly, to determine the legal issues after the enactment of the Supreme Court Regulation No. 2 of 2012.From the research, it can be concluded two main things. First, the concept of minor criminal offenses before and after the Supreme Court Regulation No. 2 of 2012 has differences and similarities within the scope of substantive criminal law and criminal law formal. Equations within the scope of substantive criminal law is related to the threat of imprisonment to perpetrators and absence of protection to victims of crime a misdemeanor. While the equations within the scope of formal criminal law is procedural law is the law used by the event quick check shows. Differences in the scope of the substantive criminal law is not entirely change the provisions regarding misdemeanor. While the differences in the scope of the formal criminal law is subject to arrest offenders if the value of the goods or money is the object of the case more than Rp. 250, -. After the enactment of the Supreme Court, offenders subject to arrest if the value of the goods or money is the object of the case more than Rp. 2.500.000, -. Second, the legal issues after the enactment of the Supreme Court is still a violation of human rights because of the persistence of the detention of minor criminals, without exception to the prosecutor's indictment then the case will still be processed, checked by regular inspection and the case is not considered as a follow-criminal misdemeanor, and lack of socialization to the public prosecutor so as not to indict the Supreme Court according to Regulation (wrong in making the accusation).Keywords: Supreme Court Rules-Theft Light